Asymmetric impact of economic value-added dynamics on market value of stocks in Pakistan stock exchange, a new evidence from panel co-integration, FMOLS and DOLS - Adil Pasha; Muhammad Ramzan (Cogent Business & Management, 2019)
Shareholders' wealth maximization is the ultimate objective of firms. Economic value added (EVA) is a financial metric linked to shareholders' wealth maximization. Prior studies revealing the efficacy of value-based and accounting-based performance measures are inconclusive. Moreover, all prior research ignored long-run and short-run co-integration of traditional as well as value-based financial performance measures with share prices. This research found EVA has a negative weak but significant relation with stock return in long run by employing panel co-integration, panel FMOLS and panel DOLS for 70 nonfinancial Pakistan Stock Exchange listed firms from 13 industries for a study period of 2006-2015.
Keywords: 650; EVA; ROA; Stock Returns; FMOLS; DOLS